Pengaruh Kekuatan Ortodontik terhadap Resorpsi Akar Gigi pada Gigi dengan Perawatan Endodontik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Apical root resorption is one of the most common iatrogenic problems associated with orthodontic treatment, particularly in incisivi. Many factors were suspected as aetiologic factors for existing root resorption, i e: traumatic history before treatment, exessive orthodontic force, hormonal and genetic factors, and endodontic treatment. The purpose of the study was to determine wether vital and endodontically treated teeth exhibit a similar severity of apical root resorption in response to orthodontic treatment. The conclusion is, some reseachers found that vital teeth resorbed to a significantly greater degree than teeth served as a control, and others found no difference between them. There are many efforts in orthodontic treatment can do to minimalized apical root resorption in endodontically treated teeth , ie : considering traumatic history before treatment and using lighter orthodontic force.